ENTREPRENEURSHIP: STRATEGI PEMASARAN DAN PENGEMBANGAN PRODUK USAHA RUMAH BATIK SETU DI TANGERANG SELATAN - rodhiah diah diah; M Tony Nawawi Tony Nawawi; Toto Mujio Mukmin Mujio Mukmin (Jurnal Bakti Masyarakat Indonesia, 2021)
PKM activities are a continuation of previous activities. Where this advanced entrepreneurship program is focused on training activities on marketing and product development. The partner in the activity is the Setu batik home business cooperative group in South Tangerang. Given that there are still partners' problems regarding marketing strategies and product development that have not been carried out optimally. For this reason, PKM activities aim to provide understanding to partners about marketing strategies and product development strategies, so that partners can have knowledge in increasing batik sales. The method used includes: training in marketing theory and product development. Provide assistance in preparing product development steps. The results of the activity indicated that there was an increase in partners' knowledge about marketing and product development. The training provided on marketing strategies, namely product strategy, price, place and promotion has run smoothly. Training and socialization on product development, and entrepreneurship programs have been conducted in accordance with the needs of partners. Includes an explanation of the stages of product development consisting of: Idea generation; Idea screening;. Development and Testing concept;Marketing strategy development;Business analysis; Product development;Market testing and Commercialization. This training has provided partner insights for new product development with simple motives. Furthermore, partners can develop products in an effort to increase the variety of products to be sold ABSTRAK:Kegiatan PKM merupakan kelanjutan dari kegiatan sebelumnya. Program enterpreneurship lanjutan ini  difokuskan pada kegiatan pelatihan tentang pemasaran dan pengembangan produk . Mitra yang menjadi tempat kegiatan adalah kelompok koperasi usaha rumah batik Setu di Tangerang Selatan. Mengingat masih adanya permasalahan mitra tentang strategi pemasaran dan pengembangan produk belum dilakukan secara optimal. Untuk itu kegiatan PKM bertujuan memberikan pemahaman pada mitra tentang strategi pemasaran dan strategi pengembangan produk, agar mitra dapat memiliki bekal pengetahuan dalam meningkatkan penjualan batik. Metode yang dilakukan meliputi:pelatihan teori pemasaran,dan pengembangan produk. Melakukan  pendampingan dalam menyusun langkah langkah pengembangan produk. Hasil kegiatan menunjukkan terjadi peningkatan pengetahuan mitra tentang pemasaran Pelatihan yang diberikan tentang  strategi pemasaran yaitu strategi produk, price,place dan promotion telah berjalan dengan lancar. Pelatihan dan sosialisasi tentang pengembangan produk, dan program entrepreneurship telah dilakukan sesuai dengan  kebutuhan mitra. Meliputi penjelasan tahapan pengembangan produk terdiri dari:  Idea generation (Pemunculan gagasan).  Idea screening (Penyaringan gagasan) .  Concept development and testing (Pengembangan dan Pengujian konsep.)  Marketing strategy development (Pengembangan strategi pemasaran). Business analysis (Analisis bisnis). Product development (Pengembangan produk), Market testing (Pengujian pasar) dan Commercialization (Komersialisasi). Pelatihan ini telah memberikan wawasan mitra untuk pengembangan produk baru dengan motif yang sederhana. Selajutnya mitra dapat melakukan  pengembangan produk dalam upaya meningkatkan variasi produk yang akan dijual